2015
DOI: 10.5465/amj.2013.0750
|View full text |Cite
|
Sign up to set email alerts
|

Gender Diversity and Securities Fraud

Abstract: We formulate theory on the effect of board of director gender diversity on the broad spectrum of securities fraud and generate three main insights. First, based on ethicality, risk aversion, and diversity, we hypothesize that gender diversity on boards can operate as a significant moderator for the frequency of fraud. Second, we hypothesize that the stock market response to fraud from a more gender-diverse board is significantly less pronounced. Third, we hypothesize that women are more effective in maledomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
382
5
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(411 citation statements)
references
References 93 publications
18
382
5
6
Order By: Relevance
“…It is also worth noticing that a wide range of factors influence corporate culture. In addition to the differences in regional culture documented in our study, the gender of CEO or gender diversity of board composition also affects corporate culture in China (Cumming, Leung, & Rui, 2015;McGuinness, Vieito, & Wang, 2017).…”
Section: Robustness Analysismentioning
confidence: 73%
“…It is also worth noticing that a wide range of factors influence corporate culture. In addition to the differences in regional culture documented in our study, the gender of CEO or gender diversity of board composition also affects corporate culture in China (Cumming, Leung, & Rui, 2015;McGuinness, Vieito, & Wang, 2017).…”
Section: Robustness Analysismentioning
confidence: 73%
“…Li et al, 2017), has become especially important. Despite evidence that women directors help with nonfinancial performance such as CSR and sustainability (Li et al, 2017), and related concerns over the ethical and financial concerns (Carter, D'Souza, Simkins, & Simpson, 2010;Cumming, Leung, & Rui, 2015) arising from a lack of gender diversity, the presence of female directors remains quite low (Lewellyn & Muller-Kahle, 2019), and there is increasing pressure globally to enhance the percentage of female directors on the board. Many countries have chosen to adopt either a coercive, enabling, or laissez-faire approach (Labelle, Francoeur, & Lakhal, 2015).…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…Also, women are more diligent than men that help to improve monitoring (Kirsch, 2017). In particular, several papers show that women are more ethical, risk-adverse, more prepared, and long-term oriented than men (Cumming et al, 2015;Franke, Crown, & Spake, 1997;Pan & Sparks, 2012). For example, Pan and Sparks (2012) contend that women directors are firmer than male directors when it comes to implementing moral standards on the board.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In this paper, we focus on the effect of women on the remuneration committee as previous studies have shown women are more likely to be effective monitors (Adams & Ferreira, 2009;Carter, Simkins, & Simpson, 2003), more ethical (Cumming, Leung, & Rui, 2015), and more likely to reduce information asymmetry (Abad, Lucas-Pérez, Minguez-Vera, & Yagüe, 2017;Srinidhi, Gul, & Tsui, 2011). In addition, there are presently limited studies on the effect of women on the remuneration committee (Kirsch, 2017;Obermann & Velte, 2018).…”
Section: Introductionmentioning
confidence: 99%